Patulin-producing molds in corn silage and high moisture corn and effects of patulin on fermentation by ruminal microbes in continuous culture - Tapia, Maria Ofelia (2005)
The objectives were to investigate the presence of patulin-producing Penicillium sp. in corn silage and high moisture corn as well as adverse effects of patulin on microbial fermentation in continuous culture fermenters. Eighty-three samples of corn silage or high moisture corn were cultured to determine the presence of molds. Penicillium sp. were isolated from 0.82 of samples. Of these Penicillium sp. isolates, 0.03 produced patulin on yeast extract sucrose and potato dextrose agar. The patulin-producing isolates belonged to the P. viridicatum group. The other molds identified were: Mucor sp. (0.45), Aspergillus sp. (0.41), and Fusarium sp. (0.25). Eight single-flow continuous culture fermenters were used to study effects of patulin on fermentation by ruminal microbes. Two 1-l fermenters were supplemented with 0, 10, 20 or 40 mg of patulin every 12 h for three consecutive days. Increasing patulin reduced neutral detergent and acid detergent fiber digestibility at a decreasing rate (linear, P < 0.01; quadratic, P < 0.05). True digestion of organic matter and total non-structural carbohydrates decreased linearly (P < 0.05) as patulin concentration increased. Crude protein digestion and bacterial N flows decreased linearly (P < 0.05). Conversely, there was a linear increase (P < 0.05) in ammonia nitrogen with increased patulin. Total, ammonia and non-ammonia N flows were not affected by patulin. Efficiency of microbial protein synthesis was not affected by patulin but there was a linear decreased (P < 0.05) in the efficiency of N utilization. Increasing patulin levels caused a linear decrease (P < 0.001) of total volatile fatty acid concentration and a quadratic decrease of acetate and propionate molar proportions (P < 0.05). Ten and 20 mg/l of patulin produced a decrease in acetate proportion and an increase in propionate proportion. Lactate concentration (mmol/l) increase from 0.0 to 216.5 mmol/l (linear, P < 0.05) with increasing patulin concentration. Penicillium sp. molds are common contaminants of corn silage and high moisture corn and they produce patulin that can adversely affect fermentation by ruminal microbes. Alterations in microbial digestion of dry matter, and production of microbial end products, impact the production and/or health of ruminants.